2010
DOI: 10.1097/iae.0b013e3181c59725
|View full text |Cite
|
Sign up to set email alerts
|

Macular Functional Changes Evaluated With Mp-1 Microperimetry After Intravitreal Bevacizumab for Subfoveal Myopic Choroidal Neovascularization

Abstract: Improvement of macular sensitivity and fixation stability 1 year after intravitreal bevacizumab for myopic choroidal neovascularization suggest a stable and progressive macular function recovery. The mean treatment session was 1.53, with 53.3% of patients needing only a single intravitreal bevacizumab injection, supporting a potential long-lasting efficacy of intravitreal bevacizumab treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
0
18
0
3
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22] However, the follow-up periods were up to 1-year in most of the earlier studies. There have been a few studies that showed 2-years visual outcomes of IVB for mCNV, and the results have been conflicting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22] However, the follow-up periods were up to 1-year in most of the earlier studies. There have been a few studies that showed 2-years visual outcomes of IVB for mCNV, and the results have been conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…6 Because of the poor natural history of mCNVs, several procedures have been tried to treat mCNVs, for example, thermal laser photocoagulation, 7 photodynamic therapy (PDT) with verteporfin (Visudyne, Novartis Pharma AG, Basel, Switzerland), 8 and intravitreal bevacizumab (Avastin; Genentech, South San Francisco, CA, USA), a recombinant humanized monoclonal anti-VEGF antibody. Earlier case series have reported good visual outcomes 1 to 2 years after intravitreal bevacizumab (IVB), [9][10][11][12][13][14][15][16][17][18][19][20][21] and at present IVB would be the first-line therapy for sub-and juxtafoveal mCNVs. 22 However, there is still not enough information to predict the visual outcome of each patient with mCNV treated with IVB.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Although the short-term results have demonstrated significant visual improvement following anti-VEGF therapy, the longer term visual outcomes appeared more variable. 14,[26][27][28] In addition, many previous studies have included both treatment naïve cases and previously treated eyes, as well as subfoveal and non-subfoveal CNV in the series, making comparison of results more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, the long-term outcome of PDT is not favourable as patients generally had no improvement in mean visual acuity following treatment and the beneficial effect of PDT in preventing visual loss was no longer significant at 2 years. 6,7 In the past few years, various studies have demonstrated the short-term efficacy of intravitreal antivascular endothelial growth factor (VEGF) agents in treating myopic CNV, including both bevacizumab [8][9][10][11][12][13][14][15][16][17][18] and ranibizumab. [18][19][20][21][22][23][24][25] Most of the studies have demonstrated significant mean visual improvement after anti-VEGF therapy and the beneficial effects were maintained at 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…However, a functional improvement was registered performing microperimetry studies at 6 and 12 months [177,178]. …”
Section: Treatment Of Myopic Cnvmentioning
confidence: 99%